The LINC complex in blood vessels: from physiology to pathological implications in arterioles - Ferreira, Gonzalo; Cardozo, Romina; Chavarria, Luisina; Santander, Axel; Sobrevia, Luis [UNESP]; Chang, Wakam; Gundersen, Gregg; Nicolson, Garth L. (Wiley, 2025)
The LINC (linker of nucleoskeleton and cytoskeleton) complex is a critical component of the cellular architecture that bridges the nucleoskeleton and cytoskeleton and mediates mechanotransduction to and from the nucleus. Though it plays important roles in all blood vessels, it is in arterioles that this complex plays a pivotal role in maintaining endothelial cell integrity, regulating vascular tone, forming new microvessels and modulating responses to mechanical and biochemical stimuli. It is also important in vascular smooth muscle cells and fibroblasts, where it possibly plays a role in the contractile to secretory phenotypic transformation during atherosclerosis and vascular ageing, and in fibroblasts' migration and inflammatory responses in the adventitia. Physiologically, the LINC complex contributes to the stability of arteriolar structure, adaptations to changes in blood flow and injury repair mechanisms. Pathologically, dysregulation or mutations in LINC complex components can lead to compromised endothelial function, vascular remodelling and exacerbation of cardiovascular diseases such as atherosclerosis (arteriolosclerosis). This review summarizes our current understanding of the roles of the LINC complex in cells from arterioles, highlighting its most important physiological functions, exploring its implications for vascular pathology and emphasizing some of its functional characteristics in endothelial cells. By elucidating the LINC complex's role in health and disease, we aim to provide insights that could improve future therapeutic strategies targeting LINC complex-related vascular disorders. (Figure presented.).
Keywords: arterioles; endothelial cells; LINC complex